Trimetallic@Cyclodextrin Nanocomposite: Photocatalyst for Degradation of Amoxicillin and Catalyst for Esterification Reactions - Gaurav Sharma; Alberto García-Peñas; Mu. Naushad; Amit Kumar; Mika Sillanpää; Forian J. Stadler (Journal of Chemistry)
The industry is looking for new materials which can respond to specific applications that exclusively advance materials can provide. In this context, nanoparticles and nanocomposites opened an interesting method for designing specific properties which can be modulated according to the requirements. The preparation of biomolecules supported trimetallic nanoparticles and some other derives is a good example of the complex systems that can be designed for getting exclusive properties. This study is based on the preparation of new cyclodextrin supported Fe/La/Zn trimetallic nanocomposite by the microemulsion technique. Photocatalytic degradation of amoxicillin was performed using cyclodextrin-Fe/La/Zn. 78% of amoxicillin photodegradation along 4 hours of photoirradiation was achieved. Finally, the catalytic nature of new material was explored for oxidation and esterification reactions. The present study revealed that this advanced multifunctional nanomaterial can be successfully employed for environmental remediation and catalytic activities.